The impact of irrelevant auditory facial descriptions on memory for target faces: implications for eyewitness memory. Issue 4 (9th November 2015) - Marsh, John E.; Demaine, Jack; Bell, Raoul; Skelton, Faye C.; Frowd, Charlie D.; Röer, Jan P.; Buchner, Axel
Abstract : Purpose: – The purpose of this paper is to investigate the potential susceptibility of eyewitness memory to the presence of extraneous background speech that comprises a description consistent with, or at odds with, a target face. Design/methodology/approach: – A between-participants design was deployed whereby participants viewed an unfamiliar target face in the presence of quiet, or extraneous to-be-ignored speech comprising a verbal description that was either congruent or incongruent with the target face. After a short distractor task, participants were asked to describe the target face and construct a composite of the face using PRO-fit software. Further participants rated the likeness of the composites to the target. Findings: – Recall of correct facial descriptors was facilitated by congruent to-be-ignored speech and inhibited by incongruent to-be-ignored speech compared to quiet. Moreover, incorrect facial descriptors were reported more often in the incongruent speech condition compared with the congruent speech and quiet conditions. Composites constructed after exposure to incongruent speech were rated as worse likenesses to the target than those created after exposure to congruent speech and quiet. Whether congruent speech facilitated or impaired composite construction was found to depend on the distinctiveness of the target face. Practical implications: – The results suggest that the nature of to-be-ignored background speech has powerful effects on the accuracy of information verbally reported from having witnessed a face. Incongruent speech appears to disrupt the recognition processes that underpin face construction while congruent speech may have facilitative or detrimental effects on this process, depending on the distinctiveness of the target face. Originality/value: – This is one of the first studies to demonstrate that extraneous speech can produce adverse effects on the recall and recognition of complex visual information: in this case, the appearance of a human face.